Empowering Communities through Skills Training to Improve Local Economy - Moh Ali Fauzi; Yuni Masrifatin; Indrasari, Meithiana; Abioye, Abdalah (Bisma : Bimbingan Swadaya Masyarakat, 2025)
This study investigates the impact of skills training programs on community empowerment and local economic development in Rejoso Village, East Java. The training focused on local resource utilization, entrepreneurship, and digital skills development, aiming to address skill gaps and enhance socio-economic conditions. Using the Participatory Action Research (PAR) methodology, the research engaged community members throughout the planning, implementation, and evaluation phases. The findings reveal that the training programs significantly improved participants' knowledge and practical skills, leading to the creation of new businesses and an increase in household income. Additionally, the programs fostered social empowerment, particularly among women, by enhancing their self-reliance and confidence. However, challenges such as limited access to capital and technological barriers were identified, underscoring the need for continued support and resources. This research contributes to the understanding of community-driven empowerment initiatives as effective tools for sustainable local economic development.